Cognitive Function Mediates the Anti-suicide Effect of Repeated Intravenous Ketamine in Adult Patients With Suicidal Ideation - Zhou, Yanling; Wang, Chengyu; Lan, Xiaofeng; Li, Weicheng; Chao, Ziyuan; Wu, Kai; McIntyre, Roger S.; Ning, Yuping (Frontiers in Psychiatry, 2022)
Objective: Prior research has shown that ketamine has anti-suicide effects. Additional evidence also suggests that ketamine may offer pro-cognitive effects. Herein, we propose that the anti-suicide effects of ketamine are partially mediated via pro-cognitive effects. We aimed to determine whether improvement in cognitive function mediated change in suicidal ideation was associated with ketamine treatment. Methods: Unipolar or bipolar depressive patients (n=86) with suicidal ideation received six infusions of ketamine (0.5mg/kg) over two weeks. Current severity of suicidal ideation and depression symptoms were assessed with the Beck Scale for Suicide Ideation (SSI) and the Montgomery–Asberg Depression Rating Scale (MADRS) respectively at baseline, day 13 and day 26. Cognitive domains, including processing speed, working memory, visual learning and verbal learning were measured with the Measurement and Treatment Research to Improve Cognition in Schizophrenia (MATRICS) Consensus Cognitive Battery at the same time-points. Results: Mediation analysis showed a significant total effect of ketamine treatment on SSI score (coef=-1.853, 95%CI [-2.2, -1.5]). The direct and total indirect (MADRS total score and any of cognitive domains) effects of ketamine on suicidal ideation both were statistically significant (direct: coef=-1.064~-1.352; total indirect: coef=-0.501~-0.788). MADRS total score and processing speed (but not other cognitive domains) were significant partial mediators of the association between ketamine treatment and improvements in suicidal ideation. Conclusion: Depressive symptoms severity and processing speed performance partially mediated improvements in suicidal ideation after repeated ketamine infusions in persons with unipolar or bipolar depressive disorder.